2014
DOI: 10.4186/ej.2014.18.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Particle Packing Approach for Designing the Mortar Phase of Self Compacting Concrete

Abstract: Self Compacting Concrete (SCC) is a tailored concrete mix, strongly dependent on the constituent proportions and the physical characteristics of the constituents. In order to achieve the self compacting concrete, mortar phase plays a vital role as it contributes to the active suspension phase of aggregates. High powder content and optimum fine aggregate is required for the desired flowability and stability of mortar. Hence, for accomplishing a self compacting concrete, the design of paste and mortar phase need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…According to previous studies that used mini-slump and Marsh cones [57][58][59][60], good paste properties correspond to a D flow ≥ 165 mm and a T flow ≤ 40s, depending on the ratios of the concentration of solids to the total volume V S /V T , and of the volume of water to the total volume V W /V T .…”
Section: Flowabilitymentioning
confidence: 99%
“…According to previous studies that used mini-slump and Marsh cones [57][58][59][60], good paste properties correspond to a D flow ≥ 165 mm and a T flow ≤ 40s, depending on the ratios of the concentration of solids to the total volume V S /V T , and of the volume of water to the total volume V W /V T .…”
Section: Flowabilitymentioning
confidence: 99%
“…BET surface area is measured by using a nitrogen adsorption measurements (Micromeritics, Tristar II 3020V1.03). The water demand of the binder is measured by the Punkte test [26].…”
Section: Materials Characterizationmentioning
confidence: 99%
“…However, there is limited research available on the mechanical properties of HSSCC, and further investigation is required to fully understand its potential. In recent times, there have been several studies carried out to examine the mechanical properties of HSSCC. , These studies have shown that HSSCC has improved compressive and tensile strengths compared to conventional SCC and that its mechanical properties are influenced by factors like the type of aggregates used, curing conditions, and the type of admixtures. Numerous research works have been undertaken to analyze the mechanical properties of HSSCC, including but not limited to stress–strain behavior, elastic modulus, and Poisson’s ratio. These studies have shown that the binder content, W/B ratio, and type and size of aggregates used in the mixes significantly influence the mechanical properties of HSSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there have been several studies carried out to examine the mechanical properties of HSSCC. 3 , 4 These studies have shown that HSSCC has improved compressive and tensile strengths compared to conventional SCC and that its mechanical properties are influenced by factors like the type of aggregates used, curing conditions, and the type of admixtures. Numerous research works have been undertaken to analyze the mechanical properties of HSSCC, including but not limited to stress–strain behavior, elastic modulus, and Poisson’s ratio.…”
Section: Introductionmentioning
confidence: 99%